Combining active restoration and targeted grazing to establish native plants and reduce fuel loads in invaded ecosystems. Issue 24 (11th December 2018) - Porensky, Lauren M.; Perryman, Barry L.; Williamson, Matthew A.; Madsen, Matthew D.; Leger, Elizabeth A.
Abstract: Many drylands have been converted from perennial‐dominated ecosystems to invaded, annual‐dominated, fire‐prone systems. Innovative approaches are needed to disrupt fire‐invasion feedbacks. Targeted grazing can reduce invasive plant abundance and associated flammable fuels, and fuelbreaks can limit fire spread. Restored strips of native plants (native greenstrips) can function as fuelbreaks while also providing forage and habitat benefits. However, methods for establishing native greenstrips in invaded drylands are poorly developed. Moreover, if fuels reduction and greenstrip establishment are to proceed simultaneously, it is critical to understand how targeted grazing interacts with plant establishment. We determined how targeted grazing treatments interacted with seed rate, spatial planting arrangement (mixtures vs. monoculture strips), seed coating technology, and species identity (five native grasses) to affect standing biomass and seeded plant density in experimental greenstrips. We monitored for two growing seasons to document effects during the seedling establishment phase. Across planting treatments, ungrazed paddocks had the highest second‐year seeded plant densities and the highest standing biomass. Paddocks grazed in fall of the second growing season had fewer seedlings than paddocks grazed in spring, five months later. High seed rates minimized negative effects of grazing on plant establishment. Among seeded species, Elymus trachycaulus and Poa secunda had the highest second‐year densities, but achieved this via different pathways. Elymus trachycaulus produced the most first‐year seedlings, but declined in response to grazing, whereas P. secunda had moderate first‐year establishment but high survival across grazing treatments. We identified clear tradeoffs between reducing fuel loads and establishing native plants in invaded sagebrush steppe; similar tradeoffs may exist in other invaded drylands. In our system, tradeoffs were minimized by boosting seed rates, using grazing‐tolerant species, and delaying grazing. In invaded ecosystems, combining targeted grazing with high‐input restoration may create opportunities to limit wildfire risk while also shifting vegetation toward more desirable species. Abstract : Interrupting feedbacks between wildfire and invasion is a challenge worldwide and is especially pressing in western US drylands where ecosystem conversion has occurred at broad scales. We asked whether targeted grazing could be combined with high‐input, spatially strategic restoration to create patches of self‐sustaining, fire‐resistant vegetation. We identified clear tradeoffs between restoring native plants and using livestock to reduce wildfire risk, but demonstrated that these undesirable tradeoffs can be minimized by boosting seed rates, using grazing‐tolerant species, and altering timing of grazing.